Piper sarmentosum Roxb. Attenuates Vascular Endothelial Dysfunction in Nicotine-Induced Rats - Md. Salleh, Muhd Fakh Rur Razi; Aminuddin, Amilia; Hamid, Adila A.; Salamt, Norizam; Japar Sidik, Fadhlullah Zuhair; Ugusman, Azizah (Frontiers in Pharmacology, 2021)
Exposure to cigarette smoke is an important risk factor for cardiovascular diseases. Nicotine is an addictive compound in cigarette smoke that triggers oxidative stress, which leads to vascular dysfunction. Piper sarmentosum Roxb. is a herb with antioxidant and vascular protective effects. This study evaluated the potential protective effect of the aqueous extract of P. sarmentosum leaf (AEPS) on vascular dysfunction in rats induced with prolonged nicotine administration. A total of 22 male Sprague-Dawley rats were divided into control (normal saline, oral gavage [p.o.]), nicotine (0.8 mg/kg/day nicotine, intraperitoneally [i.p.]), and nicotine + AEPS groups (250 mg/kg/day AEPS, p.o. + 0.8 mg/kg/day nicotine, i.p.). Treatment was given for 21 days. Thoracic aortae were harvested from the rats for the measurement of vasorelaxation, vascular nitric oxide (NO) level, and antioxidant level and the assessment of vascular remodeling. Rats treated with AEPS had improved vasorelaxation to endothelium-dependent vasodilator, acetylcholine (ACh), compared with the nicotine-induced rats (P<0.05). The presence of endothelium increased the maximum relaxation of aortic rings in response to ACh. Compared with the nicotine group, AEPS enhanced vascular NO level (P<0.001) and increased antioxidant levels as measured by superoxide dismutase activity (P<0.05), catalase activity (P<0.01), and reduced glutathione level (P<0.05). No remarkable changes in aortic histomorphometry were detected. In conclusion, P. sarmentosum attenuates vascular endothelial dysfunction in nicotine-induced rats by improving vasorelaxation and enhancing vascular NO and antioxidant levels.